Olympic Truce: Creating a culture of Peace - Πέππα, Διονυσία (Πανεπιστήμιο Πελοποννήσου, 2013)
The concept of the Olympic Truce, which is also known by the name ekecheiria dates back to 776 B.C. in Ancient Greece. The three kings Iphitos of Elis, Lycourgos of Sparta and Cleosthenes of Pisa agree to the tradition of the Olympic Truce and organize the first Olympic Games at Olympia. All conflicts are ceased from seven days before until seven days after the Games, ensuring the benefit of safety and peace .Taking into consideration the global political reality, in 1992 the International Olympic Committee decides to revive the Olympic Truce in order to safeguard the athlete’s interests and encourage peaceful solutions to the conflicts around the world. The goal of this study is to explore if Olympic Truce can be re-established, overcome the obstacles and contribute to the development of a global culture for peace and togetherness. It illustrates the historical and contemporary link between Olympism and Olympic Truce and underlines the valuable role of international associations and organizations. In particular, this study looks at opportunities for building a culture of peace through Sport and fostering a culture of respect, tolerance, reconciliation and solidarity through Education. It argues that sport is a powerful vehicle for achieving human development, peacemaking and peace-keeping as it is based on a unique set of values. It may play roles in changing mentalities, inspiring and mobilizing future generations. Furthermore, it examines the power of education in a pedagogical base as an important resource in promoting peace, social justice, cultural diversity and stability at a global level. Finally, it highlights the discrepancy between the theory and practice and analyzes the developments, tendencies, dynamics, existing difficulties and the future challenges of this priceless concept.
Keywords: Olympic truce; Olympics- Greece, Ancient; Olympism - Philosophy; Olympic movement; Olympism - Social aspects; Ολυμπιακή εκεχειρία; Ολυμπιακοί Αγώνες - Ελλάδα, Αρχαία; Ολυμπισμός - Φιλοσοφία; Ολυμπιακό κίνημα; Ολυμπισμός - Κοινωνικές απόψεις